The association of the goatfish mulloidichthys martinicus with the grunt haemulon chrysargyreum: an example of protective mimicry - Krajewski, João Paulo; Bonaldo, Roberta Martini; Sazima, Cristina [UNESP]; Sazima, Ivan (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2004)
A presumed example of protective mimicry between the yellow goatfish, Mulloidichthys martinicus (Mullidae) and the smallmouth grunt, Haemulon chrysargyreum (Haemulidae) is described from Fernando de Noronha Archipelago, NE Brazil. The goatfish and the grunt share a similar overall shape and colour pattern. We found that these two species regularly form mixed schools around reefs. Additionally, when chased small groups of yellow goatfish join schools of smallmouth grunts and behave like them. The colour and shape resemblances between the two species enable their mixed schooling, and enhance the protection against visually oriented predators for both of them. Thus, we suggest that the protective association herein reported for the goatfish and the grunt may be considered as a “social mimicry”, since neither species is venomous, poisonous or strongly armed. Furthermore, we suggest that additional instances of social mimicry may involve the yellow goatfish and other striped Haemulon species.

Descrevemos aqui um possível exemplo de mimetismo de proteção entre o saramunete Mulloidichthys martinicus (Mullidae) e a xira Haemulon chrysargyreum (Haemulidae), no Arquipélago de Fernando de Noronha, Nordeste do Brasil. O saramunete e a xira são semelhantes entre si, no padrão de coloração e no formato do corpo. Observamos que estas duas espécies formam cardumes mistos regularmente, ao redor de recifes. Quando perseguidos, pequenos grupos isolados de saramunetes se associam aos cardumes de xira e se comportam de modo semelhante às xiras. As semelhanças de formato e coloração entre as duas espécies provavelmente facilitam a formação de cardumes mistos e aumentam a proteção contra predadores visualmente orientados, para ambas as espécies. Assim, acreditamos que a associação protetora entre o saramunete e a xira pode ser considerada como um tipo de “mimetismo social”, uma vez que nenhuma destas espécies é venenosa, peçonhenta ou tem fortes estruturas mecânicas de defesa. Sugerimos, ainda, que exemplos adicionais de mimetismo social possam envolver o saramunete e outras espécies listradas de Haemulon.
Keywords: Protective mimicry; social mimicry; mixed schooling; Mulloidichthys martinicus; Haemulon chrysargyreum; Mimetismo de proteção; mimetismo social; cardumes mistos; Mulloidichthys martinicus; Haemulon chrysargyreum